Muscle acellular scaffold as a biomaterial: effects on C2C12 cell differentiation and interaction with the murine host environment - Perniconi, Barbara; Coletti, Dario; Aulino, Paola; Costa, Alessandra; Aprile, Paola; Santacroce, Luigi; Chiaravalloti, Ernesto; Coquelin, Laura; Chevallier, Nathalie; Teodori, Laura; Adamo, Sergio; Marrelli, Massimo; et al. (Frontiers in Physiology, 2014)
The extracellular matrix (ECM) of decellularized organs possesses the characteristics of the ideal tissue-engineering scaffold (i.e. histocompatibility, porosity, degradability, non-toxicity). We previously observed that the muscle acellular scaffold (MAS) is a pro-myogenic environment in vivo. In order to determine whether MAS, which is basically muscle ECM, behaves as a myogenic environment, regardless of its location, we analysed MAS interaction with both muscle and nonmuscle cells and tissues, to assess the effects of MAS on cell differentiation. Bone morphogenetic protein treatment of C2C12 cells cultured within MAS induced osteogenic differentiation in vitro, thus suggesting that MAS does not irreversibly commit cells to myogenesis. In vivo MAS supported formation of nascent muscle fibres when replacing a muscle (orthotopic position). However, heterotopically grafted MAS did not give rise to muscle fibres when transplanted within the renal capsule. Also, no muscle formation was observed when MAS was transplanted under the xiphoid process, in spite of the abundant presence of cells migrating along the laminin-based MAS structure. Taken together, our results suggest that MAS itself is not sufficient to induce myogenic differentiation. It is likely that the pro-myogenic environment of MAS is not strictly related to the intrinsic properties of the muscle scaffold (e.g. specific muscle ECM proteins). Indeed, it is more likely that myogenic stem cells colonising MAS recognise a muscle environment that ultimately allows terminal myogenic differentiation. In conclusion, MAS may represent a suitable environment for muscle and non-muscle 3D constructs characterised by a highly organised structure whose relative stability promotes integration with the surrounding tissues. Our work highlights the plasticity of MAS, suggesting that it may be possible to consider MAS for a wider range of tissue engineering applications than the mere replacement of volumetric muscle loss.